Electrochemical polishing solution for laser additive manufacturing alloy material and polishing method thereof

By using electrochemical polishing liquid containing choline chloride and ethylene glycol on laser additive manufacturing alloy materials, combined with masking agent and surfactant, the problem of high roughness of the special-shaped alloy material is solved, and selective polishing and Efficient and smooth processing.

CN119243306APending Publication Date: 2025-01-03AVIC BEIJING INST OF AERONAUTICAL MATERIALS
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411301684.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The special-shaped alloy material obtained by laser additive manufacturing has too high roughness, and traditional mechanical polishing methods are not applicable. The chemical polishing liquid is corrosive and cannot selectively corrode the protruding parts, resulting in lack of smoothness and brightness.

Method used

Using an electrochemical polishing liquid, including the molar ratio of choline chloride and ethylene glycol is 1:1.8 to 2.2, and a masking agent and surfactant are added, and the electrochemical polishing treatment is used to utilize choline chloride and ethylene glycol. The upper convex part of the workpiece surface is polished, and the masking agent and surfactant form a protective layer to avoid unnecessary corrosion.

Benefits of technology

It realizes selective polishing of laser additive-made special-shaped alloy materials, reduces roughness, improves smoothness and brightness, is simple to operate and high efficiency, and is suitable for complex shape workpieces.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243306A_ABST
    Figure CN119243306A_ABST
Patent Text Reader

Abstract

The invention discloses an electrochemical polishing solution for a laser additive manufacturing alloy material and a polishing method of the electrochemical polishing solution, and belongs to the technical field of alloy material polishing treatment. The problem that the roughness of an alloy material obtained through existing laser additive manufacturing is too high is solved. The electrochemical polishing solution for the laser additive manufacturing alloy material, provided by the invention, comprises choline chloride and ethylene glycol, the molar ratio of choline chloride to ethylene glycol is 1: (1.8-2.2). The electrochemical polishing solution provided by the invention can be used for carrying out polishing treatment on the laser additive manufacturing special-shaped alloy material, and finally, the surface flatness of a workpiece can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of alloy material polishing, and in particular to an electrochemical polishing liquid and a polishing method for laser additive manufacturing alloy materials. Background Art

[0002] SLM additive manufacturing, namely selective laser melting technology, is a cutting-edge 3D printing method. Since SLM additive manufacturing can achieve high-precision manufacturing, has the characteristics of a wide range of material selection and rapid prototyping, it also has significant advantages in saving resources and reducing waste. It can minimize the waste of raw materials and has been widely used in the preparation of alloy materials.

[0003] However, additive manufacturing is not "free" manufacturing, and the forming capacity of the equipment is affected by many factors. Taking SLM as an example, the overhanging structure whose angle between the surface and the horizontal direction is lower than the critical value requires support material, and this critical value is usually 45°. From the principle of additive manufacturing and the raw materials used, it can be seen that when processing the overhanging part, its lower layer is powder and other materials, which cannot provide it with sufficient support and heat transfer path, and the structure is prone to collapse or warping. Although adding support structures can solve these problems, it means additional material loss, increased forming time and post-processing work, and may also affect the internal stress distribution of the part. When measuring the surface roughness of the upper and lower epidermis of inclined thick-walled samples, the following is usually observed: as the angle θ (the angle between the lower surface of the sample and the printing base) decreases, the roughness of the lower surface increases. Therefore, when using SLM additive manufacturing to print complex special-shaped alloy materials, there is often a problem of excessive roughness.

[0004] Special-shaped alloy materials are not suitable for mechanical polishing, and the traditional chemical polishing liquid system is highly corrosive. Under the action of strong acid corrosion, the surface will quickly become over-corroded, and the raised parts cannot be selectively corroded, resulting in the inability to reduce the roughness. This is manifested as the inability to achieve a polishing effect on the laser additive manufacturing alloy material, that is, the smoothness and brightness of the sample after polishing are lacking. Summary of the invention

[0005] In view of the above analysis, the present invention aims to provide an electrochemical polishing liquid and a polishing method for laser additive manufacturing alloy materials, so as to solve the problem of excessive roughness of special-shaped alloy materials obtained by existing laser additive manufacturing.

[0006] The purpose of the present invention is mainly achieved through the following technical solutions:

[0007] On the one hand, the present invention provides an electrochemical polishing liquid for laser additive manufacturing of alloy materials, wherein the laser additive manufacturing of alloy materials is laser additive manufacturing of special-shaped alloy materials;

[0008] The electrochemical polishing liquid comprises choline chloride and ethylene glycol; the molar ratio of choline chloride to ethylene glycol is 1:1.8-2.2.

[0009] In one possible design, the molar ratio of choline chloride to ethylene glycol in the electrochemical polishing solution is 1:2.

[0010] In one possible design, the electrochemical polishing solution further includes a masking agent and a surfactant.

[0011] In one possible design, the molar ratio of choline chloride, masking agent and surfactant in the electrochemical polishing solution is 1:0.01-0.1:0.01-0.1.

[0012] In one possible design, the masking agent is citric acid or tartaric acid.

[0013] In a possible design, the surfactant is a betaine-type amphoteric surfactant or sodium dodecylbenzene sulfonate.

[0014] On the other hand, the present invention also provides an electrochemical polishing method for laser additive manufacturing alloy materials, using the above-mentioned electrochemical polishing solution, the electrochemical polishing method comprises the following steps:

[0015] Step 1, performing surface pretreatment on the laser additive manufacturing alloy material;

[0016] Step 2: Immerse the surface pretreated laser additive manufacturing alloy material in an electrochemical polishing solution for electrochemical polishing treatment, and complete the polishing of the laser additive manufacturing alloy material after the treatment.

[0017] Furthermore, in step 1, the surface pretreatment includes sequentially cleaning, degreasing and water washing the laser additively manufactured alloy material.

[0018] Furthermore, in step 1, during degreasing, the laser additively manufactured alloy material is placed in an acetone solution for cleaning and degreasing.

[0019] Further, in step 1, the laser additive manufacturing alloy material includes GH3536 alloy or GH4169 alloy.

[0020] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0021] (1) The present invention uses a masking agent and a surfactant to cover the concave part of the workpiece surface to form a protective layer, and uses choline chloride and ethylene glycol to polish the convex part of the workpiece surface, and finally realizes the selective polishing of laser additive manufacturing special-shaped alloy materials by electrochemical polishing liquid.

[0022] (2) The electrochemical polishing method disclosed in the present invention has low requirements on the shape of the workpiece, can meet the polishing requirements of special-shaped alloy materials, and has little impact on the workpiece.

[0023] (3) The electrochemical polishing method disclosed in the present invention is highly efficient, simple to operate, can achieve good polishing effect, and has great promotion and application value.

[0024] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the embodiments of the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0026] Figure 1a This is the scanning electron microscope image of the vertical channel sample before electrochemical polishing;

[0027] Figure 1b This is the scanning electron microscope image of the vertical channel sample after electrochemical polishing;

[0028] Figure 1c for Figure 1a and Figure 1b Image acquisition points;

[0029] Figure 2a The surface morphology of the vertical channel sample before electrochemical polishing was measured using the NT1100 profilometer (see the image acquisition point for details). Figure 1c );

[0030] Figure 2b The surface morphology of the vertical channel sample after electrochemical polishing was measured using the NT1100 profilometer (see the image acquisition point for details). Figure 1c );

[0031] Figure 3a This is the scanning electron microscope image of the curved flow channel sample 1 before electrochemical polishing;

[0032] Figure 3b This is a scanning electron microscope image of the curved flow channel sample 1 after electrochemical polishing;

[0033] Figure 3c for Figure 3a and Figure 3b Image acquisition points;

[0034] Figure 4aThis is the scanning electron microscope image of the curved flow channel sample 2 before electrochemical polishing;

[0035] Figure 4b This is the scanning electron microscope image of the curved flow channel sample 2 after electrochemical polishing;

[0036] Figure 4c for Figure 4a and Figure 4b Image acquisition points;

[0037] Figure 5a The surface morphology of curved channel sample 2 before electrochemical polishing was measured using the NT1100 profilometer (see the image acquisition point for details). Figure 4c );

[0038] Figure 5b The surface morphology of curved channel sample 2 after electrochemical polishing was measured using the NT1100 profilometer (see the image acquisition point for details). Figure 4c );

[0039] Figure 6 Schematic diagram of samples used in the embodiments and comparative examples.

[0040] Figure 7 Schematic diagram of electrochemical polishing process;

[0041] Figure 8 This is a physical picture of the electrochemical polishing device. DETAILED DESCRIPTION

[0042] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0043] On the one hand, the present invention provides an electrochemical polishing liquid for laser additive manufacturing of alloy materials, the electrochemical polishing liquid comprising choline chloride and ethylene glycol; the molar ratio of choline chloride to ethylene glycol is 1:1.8-2.2.

[0044] The above-mentioned laser additive manufacturing alloy material is a GH3536 high-temperature special-shaped alloy material, which is a GH3536 high-temperature special-shaped alloy material formed by laser selective melting (SLM), and its components and mass percentages are: Cr 19.5%-21.2%, Mo 8.02%-10.4%, Fe 17.79%-19.4%, Co1.32%-1.54%, C 0.11%-0.13%, W 0.55%-0.71%, Mn 0.02%-0.03%, Si0.3%-0.35%, and the rest is Ni.

[0045] Furthermore, the components and mass percentages of the GH3536 high-temperature alloy material formed by the above-mentioned laser selective melting are: Cr 20.5%, Mo 9.02%, Fe 18.79%, Co 1.52%, C 0.12%, W 0.6%, Mn 0.02%, Si0.3%, and the rest is Ni; the forming equipment model is SLM-100, used in a nitrogen protection environment, the laser power is 200W, the scanning speed is 1000mm / s, the layer thickness is 30μm, the scanning spacing is 60μm, the scanning strategy is zigzag line-by-line scanning, and the deflection angle between adjacent layers is 67°.

[0046] It should be noted that in the above electrochemical polishing solution, choline chloride has the structural characteristics of quaternary ammonium salt, a wide electrochemical window, high conductivity, and good polishing effect. Ethylene glycol can increase the viscosity and stability of the electrochemical polishing solution, and its cost is low. The electrochemical polishing solution of the present invention can significantly reduce the roughness of the alloy material manufactured by laser additive manufacturing.

[0047] Choline chloride and ethylene glycol are important components of electrochemical polishing liquid, which can achieve a high degree of flatness on the metal surface to be polished. During the polishing process, choline chloride as a catalyst can promote the oxidation of the metal surface, and ethylene glycol has good solubility and lubricity, which helps to improve the polishing efficiency and quality. In addition, choline chloride and ethylene glycol can reduce scratches and other surface defects generated during the polishing process.

[0048] In order to further improve the polishing effect of the electrochemical polishing liquid, the molar ratio of choline chloride to ethylene glycol in the electrochemical polishing liquid of the present invention is 1:1.85-2.15, for example, 1:1.85, 1:1.9, 1:1.95, 1:2, 1:2.05, 1:2.1, 1:2.15; controlling the electrochemical polishing liquid within the above range can obtain a better polishing effect.

[0049] Compared with the prior art, the present invention controls the molar ratio of choline chloride to ethylene glycol within the above range to better balance the catalytic ability of choline chloride and the solubility of ethylene glycol. If the ethylene glycol content is too much, the viscosity of the polishing liquid will be reduced, thereby affecting the polishing effect; if the choline chloride content is too much, the cost of the polishing liquid will be increased and the solubility of the polishing liquid will be insufficient.

[0050] The electrochemical polishing solution also includes a masking agent and a surfactant, wherein the molar ratio of choline chloride, the masking agent and the surfactant is 1:0.01-0.1:0.01-0.1.

[0051] In the above-mentioned electrochemical polishing liquid, the masking agent is citric acid or tartaric acid; citric acid and tartaric acid can form complexes with certain metal ions in the alloy material that do not require polishing treatment, thereby preventing the metal ions from contacting with the active substances in the electrochemical polishing liquid, thereby preventing them from reacting with the active substances, and ultimately achieving a masking effect on certain metal ions.

[0052] In addition, citric acid and tartaric acid can also achieve the effect of inhibiting local corrosion, because: the alloy material and special-shaped alloy material of the present invention have a relatively complex structure, and on the surface of a workpiece with a complex structure, the electrochemical properties of different regions are different. The citric acid and tartaric acid of the present invention can inhibit those regions that are easily over-polished or corroded, thereby making the polishing of the entire workpiece surface more uniform. In addition, by accurately controlling local corrosion, the masking agent helps to improve the surface quality and dimensional accuracy of the final product.

[0053] In the electrochemical polishing liquid, the surfactant is a betaine-type amphoteric surfactant or sodium dodecylbenzene sulfonate; wherein the betaine-type amphoteric surfactant is composed of a quaternary ammonium salt-type cation part and a carboxylate-type anion part.

[0054] Compared with the prior art, the betaine-type amphoteric surfactant and sodium dodecylbenzene sulfonate of the present invention have the following effects: (1) reducing the surface tension of the alloy material, so that the polishing liquid can better wet the workpiece surface, thereby increasing the contact area between the polishing liquid and the workpiece surface and enhancing the polishing effect. (2) Both the betaine-type amphoteric surfactant and sodium dodecylbenzene sulfonate help to disperse the metal ions or other particulate matter generated during the polishing process, preventing them from redepositing on the workpiece surface and causing scratches or contamination. (3) During the polishing process, there will be oil stains or other water-insoluble substances. The emulsifying effect of the surfactant can make these substances evenly dispersed in the polishing liquid, making it easy to clean and remove. (4) The surfactant of the present invention can also improve the overall stability of the polishing liquid, prevent the components in the polishing liquid from separating or precipitating, thereby extending the service life of the polishing liquid.

[0055] Since the roughness of laser additively manufactured special-shaped alloy materials is relatively large, its surface has concave parts and convex parts. Compared with the convex parts, the concave parts are more easily contacted and combined with masking agents and surfactants, so that the masking agents and surfactants cover the concave parts of the workpiece surface to form a protective layer, thereby effectively preventing the acidic components in the polishing liquid from contacting the alloy in the concave parts, thereby avoiding unnecessary corrosion. The electrochemical polishing liquid mainly polishes the convex parts of the laser additively manufactured special-shaped alloy materials, and finally realizes the selective polishing of the electrochemical polishing liquid.

[0056] It should also be emphasized that surfactants can also reduce the surface tension of the liquid, allowing the electrochemical polishing liquid to more easily wet the metal surface to be polished, which is beneficial to the protection of the concave part and further realizes the selective polishing of the electrochemical polishing liquid.

[0057] It should be noted that the higher the roughness of the initial surface of the laser additively manufactured special-shaped alloy material, the higher the polishing efficiency. This is because the higher the surface roughness of the alloy material, the more high potential difference areas there are on its surface, so the driving force for polishing is stronger, such as Figure 7 As shown in the figure, the polishing efficiency of laser additive manufacturing alloy materials with larger roughness is higher.

[0058] In another aspect, the present invention provides a method for electrochemical polishing of an alloy material produced by laser additive manufacturing, comprising the following steps:

[0059] Step 1, performing surface pretreatment on the laser additive manufacturing alloy material, taking it out after the pretreatment, washing it in water and drying it;

[0060] Specifically, the surface pretreatment includes cleaning, degreasing and water washing the laser additive manufacturing alloy material in sequence. When degreasing, the laser additive manufacturing alloy material is placed in an acetone and anhydrous ethanol solution for degreasing.

[0061] Step 2: immerse the surface pretreated laser additive manufacturing alloy material in an electrochemical polishing solution to perform electrochemical polishing treatment to complete the polishing of the laser additive manufacturing alloy material. Figure 7 shown.

[0062] In the above step 2, before placing the sample in the electrochemical polishing solution, the roughness of the sample is measured and its morphology is observed using an electron microscope.

[0063] In step 2 above, if Figure 8 As shown, pour the electrolyte into the polishing container beaker, stir the electrolyte with a magnetic stirring bar, place the polishing container on a heating base and heat it to a set temperature, then connect the sample to the positive pole of the DC power supply and immerse it in the electrolyte. Connect the cathode to the negative pole of the DC power supply and immerse it in the electrolyte, turn on the DC power supply to electrochemically polish the sample, clean and dry the sample after polishing; and perform performance tests on the chemically polished sample, measure the roughness and observe the surface morphology.

[0064] In the above step 2, the rotation speed of the magnetic stirring is 280-300rpm; the present invention can ensure that the electrochemical polishing liquid is evenly distributed on the workpiece surface through magnetic stirring, ensuring a consistent polishing effect; in addition, stirring can accelerate the contact between the polishing liquid and the workpiece surface, thereby improving the polishing efficiency and rate; furthermore, stirring can always maintain the uniformity of the components of the polishing liquid to avoid precipitation of certain components.

[0065] In the above step 2, the temperature of the electrochemical polishing treatment is 60-80° C., for example, 62° C., 64° C., 66° C., 68° C., 70° C., 72° C., 74° C., 76° C., 78° C. If the electrochemical polishing treatment temperature is lower than 60° C., the polishing rate will be reduced; if the polishing treatment temperature is higher than 80° C., excessive corrosion will occur, which is not conducive to polishing.

[0066] In the above step 2, the current density of the electrochemical polishing treatment is 50 to 80 A / dm 2 , for example, 55A / dm 2 、60A / dm 2 、65A / dm 2 、70A / dm 2 、75A / dm 2 .

[0067] In the electrochemical polishing process, current density is a key parameter, which directly affects the polishing effect and efficiency. The present invention controls the current density of the electrochemical polishing process to 50-80A / dm 2 The reason is that when the current density is greater than 80A / dm 2 It will lead to uneven surface and excessive corrosion when the current density is less than 50A / dm 2 Otherwise, the polishing speed may be slow and the effect is not obvious.

[0068] In the above step 2, the electrochemical polishing treatment time is 12 to 18 minutes, for example, 13 minutes, 14 minutes, 15 minutes, 16 minutes, and 17 minutes.

[0069] In the above step 2, the electrode spacing is 10 to 25 mm, for example, 12 mm, 14 mm, 15 mm, 16 mm, 18 mm, 20 mm, 22 mm, 24 mm; controlling the above polishing conditions is beneficial to the polishing operation.

[0070] It should be pointed out that the laser additive manufacturing alloy material of the present invention includes GH3536 alloy or GH4169 alloy.

[0071] Example 1

[0072] The laser additively manufactured GH3536 alloy workpieces (vertical flow channel specimens and curved flow channel specimens) were cleaned and then placed in an acetone solution for ultrasonic cleaning and degreasing. After degreasing, they were washed with water and dried to complete the surface pretreatment.

[0073] The workpiece after surface pretreatment was placed in an electrochemical polishing solution (the ratio of choline chloride, ethylene glycol, masking agent and surfactant in the electrochemical polishing solution was 1:2:0.05:0.05, the masking agent was citric acid, and the surfactant was a betaine-type amphoteric surfactant). The GH3536 alloy workpiece was connected to the positive electrode, and the GH3536 alloy was connected to the negative electrode of the power supply. Electrochemical polishing was performed under stirring conditions (electrochemical polishing conditions: polishing temperature 70 °C, polishing current density 60 A / dm 2 , polishing electrode spacing 15mm), after reacting for 15min, take out the GH3536 alloy workpiece and complete the electrochemical polishing operation.

[0074] Example 2

[0075] The GH3536 alloy workpiece manufactured by laser additive manufacturing was cleaned, and then placed in an acetone solution for ultrasonic cleaning and degreasing. After degreasing, it was washed with water and dried to complete the surface pretreatment. The workpiece after surface pretreatment was placed in an electrochemical polishing solution (the electrochemical polishing solution contained choline chloride, ethylene glycol, masking agent and surfactant in a ratio of 1:2:0.08:0.03, tartaric acid was used as the masking agent, and sodium dodecylbenzene sulfonate was used as the surfactant). The GH3536 alloy workpiece was connected to the positive electrode, and the GH3536 alloy was connected to the negative electrode of the power supply. Electrochemical polishing was performed under stirring conditions (electrochemical polishing conditions: polishing temperature 80°C, polishing current density 55A / dm 2 , polishing electrode spacing 20mm), after reacting for 12min, take out the GH3536 alloy workpiece and complete the electrochemical polishing operation.

[0076] Example 3

[0077] The GH3536 alloy workpiece manufactured by laser additive manufacturing was cleaned, and then placed in an acetone solution for ultrasonic cleaning and degreasing. After degreasing, it was washed with water and dried to complete the surface pretreatment. The workpiece after surface pretreatment was placed in an electrochemical polishing solution (the ratio of choline chloride, ethylene glycol, masking agent and surfactant in the electrochemical polishing solution was 1:2:0.05:0.08, the masking agent was citric acid, and the surfactant was sodium dodecylbenzene sulfonate), the GH3536 alloy workpiece was connected to the positive electrode, and the GH3536 alloy was connected to the negative electrode of the power supply, and electrochemical polishing was performed under stirring conditions (electrochemical polishing conditions: polishing temperature 60°C, polishing current density 70A / dm 2 , polishing electrode spacing 15mm), after reacting for 18min, take out the GH3536 alloy workpiece and complete the electrochemical polishing operation.

[0078] The roughness values ​​of the vertical flow channel sample and the curved flow channel sample 1 and the curved flow channel sample 2 in Example 1 before and after electrochemical polishing were respectively detected (the vertical flow channel sample sampling point 1 is Figure 1c The image acquisition points in the curved flow channel are sampling points 1. Figure 3c The image acquisition points in the curved flow channel are sampling points 2. Figure 4c The detection results are shown in Table 1.

[0079] Table 1 Roughness values ​​before and after polishing

[0080]

[0081] It can be seen from Table 1 that after electrochemical polishing, the roughness of the sample is significantly reduced. Figures 1a to 4c It can also be seen that after the electrochemical polishing treatment of the present invention, the roughness of the laser additively manufactured alloy material is significantly reduced, and it has higher smoothness and brightness. Figure 5a and 5b It can be seen that the surface of the workpiece after electrochemical polishing is relatively smooth and there are no large protrusions.

[0082] Comparative Example 1

[0083] The laser additively manufactured GH3536 alloy workpieces (vertical flow channel specimens and curved flow channel specimens) were cleaned and then placed in an acetone solution for ultrasonic cleaning and degreasing. After degreasing, they were washed with water and dried to complete the surface pretreatment.

[0084] The workpiece after surface pretreatment was placed in an electrochemical polishing solution (ethylene glycol, masking agent and surfactant in the electrochemical polishing solution were 2:0.05:0.05, the masking agent was citric acid, and the surfactant was a betaine type amphoteric surfactant). The GH3536 alloy workpiece was connected to the positive electrode, and the GH3536 alloy was connected to the negative electrode of the power supply. Electrochemical polishing was performed under stirring conditions (electrochemical polishing conditions: polishing temperature 70 ° C, polishing current density 60A / dm 2 , polishing electrode spacing 15mm), after reacting for 15min, take out the GH3536 alloy workpiece and complete the electrochemical polishing operation.

[0085] Comparative Example 2

[0086] The GH3536 alloy workpiece manufactured by laser additive manufacturing was cleaned, and then placed in an acetone solution for ultrasonic cleaning and degreasing. After degreasing, it was washed with water and dried to complete the surface pretreatment. The workpiece after surface pretreatment was placed in an electrochemical polishing solution (the ratio of choline chloride, masking agent and surfactant in the electrochemical polishing solution was 1:0.08:0.03, the masking agent was tartaric acid, and the surfactant was sodium dodecylbenzene sulfonate), the GH3536 alloy workpiece was connected to the positive electrode, and the GH3536 alloy was connected to the negative electrode of the power supply, and electrochemical polishing was performed under stirring conditions (electrochemical polishing conditions: polishing temperature 80°C, polishing current density 55A / dm 2, polishing electrode spacing 20mm), after reacting for 12min, take out the GH3536 alloy workpiece and complete the electrochemical polishing operation.

[0087] Comparative Example 3

[0088] The GH3536 alloy workpiece manufactured by laser additive manufacturing was cleaned, and then placed in an acetone solution for ultrasonic cleaning and degreasing. After degreasing, it was washed with water and dried to complete the surface pretreatment. The workpiece after surface pretreatment was placed in an electrochemical polishing solution (the electrochemical polishing solution contained choline chloride, ethylene glycol and surfactant in a ratio of 1:2:0.08, citric acid as a masking agent, and sodium dodecylbenzene sulfonate as a surfactant), the GH3536 alloy workpiece was connected to the positive electrode, and the GH3536 alloy was connected to the negative electrode of the power supply, and electrochemical polishing was performed under stirring conditions (electrochemical polishing conditions: polishing temperature 60°C, polishing current density 70A / dm 2 , polishing electrode spacing 15mm), after reacting for 18min, take out the GH3536 alloy workpiece and complete the electrochemical polishing operation.

[0089] It should be noted that the samples used in Examples 1 to 3 and Comparative Examples 1 to 3 are the same, and they all use the laser selective melting technology (SLM), the equipment uses EOS M290, and the printed samples have a width of 10 mm, a thickness of 2 mm, and a height of 10 mm (X*Y*Z). The printing angle is 45° oblique angle or 90° vertical angle, wherein the upper oblique surface of the sample is numbered 45u, and the lower oblique surface of the sample is numbered 45d, as shown in FIG. Figure 6 shown.

[0090] Compared with Example 1, Comparative Example 1 differs only in that the polishing liquid used in Comparative Example 1 does not contain choline chloride; compared with Example 2, Comparative Example 2 differs only in that the electrochemical polishing liquid used in Comparative Example 2 does not contain ethylene glycol; and compared with Example 3, Comparative Example 3 differs only in that the polishing liquid used in Comparative Example 3 does not contain a masking agent. The polishing effect data of Examples 1 to 3 and Comparative Examples 1 to 3 are listed in Table 2 below.

[0091] Table 2 Surface roughness of samples of Examples 1-3 and Comparative Examples 1-3 before and after polishing

[0092]

[0093]

[0094] Table 2 Comparison of sample speeds of Examples 1-3 and Comparative Examples 1-3

[0095]

[0096] It can be seen from Table 2 above that, firstly, compared with Example 1, since the electrochemical polishing liquid of Comparative Example 1 does not contain choline chloride, the electrochemical polishing liquid cannot effectively promote the oxidation of the metal surface, resulting in poor polishing effect. After polishing, the surface roughness of the sample upper oblique surface 45u, the sample lower oblique surface 45d and the vertical plane is significantly greater than the roughness of Example 1 of the present invention, and its roughness is relatively high; therefore, choline chloride is an indispensable component of the electrochemical polishing liquid of the present invention.

[0097] Secondly, compared with Example 2, the electrochemical polishing liquid used in Comparative Example 2 does not contain ethylene glycol, which will affect the solubility of the electrochemical polishing liquid, resulting in its polishing effect being worse than that of Example 2, and its roughness is higher; therefore, ethylene glycol is an indispensable component of the electrochemical polishing liquid of the present invention.

[0098] Furthermore, compared with Example 3, the electrochemical polishing liquid used in Comparative Example 3 does not contain a masking agent component. The use of this electrochemical polishing liquid may cause certain metal ions in the alloy material to react with the active substance, and the metal ions cannot be masked, which will affect the polishing effect.

[0099] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. An electrochemical polishing solution for laser additive manufacturing alloy materials, characterized in that: The laser additive manufacturing alloy material is a laser additive manufacturing special-shaped alloy material; The electrochemical polishing solution comprises choline chloride and ethylene glycol; the molar ratio of choline chloride to ethylene glycol is 1:1.8-2.

2.

2. The electrochemical polishing liquid for laser additive manufacturing alloy materials according to claim 1, characterized in that: The molar ratio of choline chloride to ethylene glycol in the electrochemical polishing solution is 1:

2.

3. The electrochemical polishing liquid for laser additive manufacturing alloy material according to claim 2, characterized in that: The electrochemical polishing solution also includes a masking agent and a surfactant.

4. The electrochemical polishing liquid for laser additive manufacturing alloy material according to claim 3, characterized in that: The molar ratio of choline chloride, masking agent and surfactant in the electrochemical polishing solution is 1:0.01-0.1:0.01-0.

1.

5. The electrochemical polishing liquid for laser additive manufacturing alloy material according to claim 3, characterized in that: The masking agent is citric acid or tartaric acid.

6. The electrochemical polishing liquid for laser additive manufacturing alloy material according to claim 3, characterized in that: The surfactant is a betaine type amphoteric surfactant or sodium dodecylbenzene sulfonate.

7. A method for electrochemical polishing of alloy materials manufactured by laser additive manufacturing, characterized in that: Using the electrochemical polishing solution according to any one of claims 1 to 6, the electrochemical polishing method comprises the following steps: Step 1, performing surface pretreatment on the laser additive manufacturing alloy material; Step 2: immerse the laser additive manufacturing alloy material after surface pretreatment in the electrochemical polishing liquid for electrochemical polishing treatment, and complete the polishing of the laser additive manufacturing alloy material after the treatment.

8. The electrochemical polishing method for laser additive manufacturing alloy materials according to claim 7, characterized in that: In the step 1, the surface pretreatment includes sequentially cleaning, degreasing and water washing the laser additively manufactured alloy material.

9. The electrochemical polishing method for laser additive manufacturing alloy materials according to claim 8, characterized in that: In step 1, during degreasing, the laser additively manufactured alloy material is placed in an acetone solution for cleaning and degreasing.

10. The electrochemical polishing method for laser additive manufacturing alloy materials according to claim 7, characterized in that: In the step 1, the laser additive manufacturing alloy material includes GH3536 alloy or GH4169 alloy.

Citation Information

Cited By

  • Design method for chemical polishing inner flow channel of additive manufacturing gas distributor

    CN120866827A